The association of an elevated Th/Ts ratio and lupus anticoagulant with symptomatic osteonecrosis in systemic lupus erythematosus patients - Hou, Ruihong; Lei, Jiamin; Xue, Dengfeng; Jing, Yukai; Mi, Liangyu; Guo, Qianyu; Xu, Ke; Zhang, Liyun (Frontiers in Immunology, 2024)
Objective: This study aimed to assess the risk factors for symptomatic osteonecrosis (ON) in systemic lupus erythematosus (SLE) and identify clinical characteristics and laboratory markers to predict symptomatic ON occurrence in SLE patients.Methods: Seventy (6.0%) of 1175 SLE patients diagnosed with symptomatic ON were included in this study. An equal number of SLE patients without symptomatic ON, matched in terms of age and gender, were enrolled in the control group. Clinical symptoms, routine laboratory examinations, lymphocyte subsets and treatments of these patients were retrospectively reviewed and compared between the two groups. Logistic regression analysis was employed to identify risk factors associated with symptomatic ON in SLE.Results: Among the 70 cases in the symptomatic ON group, 62 (88.6%) patients experienced femoral head necrosis, with bilateral involvement observed in 58. Bone pain was reported in 32 cases (51.6%), and 19 cases (30.6%) presented with multiple symptoms. Univariate analysis revealed significant differences between the two groups in various factors, including disease duration (months), cumulative steroid exposure time, history of thrombosis, neurological involvement, number of affected organs, myalgia/myasthenia, and usage of medications such as glucocorticoids, immunosuppressants, aspirin, and statins (P<0.05). Moreover, Lupus anticoagulant (LA) levels were significantly higher in the symptomatic ON group compared to the control group (P<0.05). Furthermore, notable distinctions were observed in peripheral blood immune cells, including an elevated white blood cell count (WBC), a decreased percentage of Ts cells (CD3+CD8+), and an elevated Th/Ts ratio. Logistic regression analysis revealed that the history of thrombosis, LA positivity, and an elevated Th/Ts ratio remained as positive factors associated with symptomatic ON (P<0.05).: Decreased Ts cells and the changes in T lymphocyte subset play an important regulatory role in the development of symptomatic ON. The history of thrombosis and LA are associated with an increased probability of symptomatic ON in SLE and may serve as a potential predictor.